Experimental Photography Study by Kurnia Ngayuga Wibowo “Memory Lane” - Abdul Aziz Al Hakim; Raden Bima Sakti Arnanda A; Rizky Dwi Andini; Khaerudin Imawan; Dedet Erawati (Journal of Social Research, 2024)
The work Experimental Photo Memory Lane by Kurnia Ngayuga Wibowo is a notable piece that has been featured in various prestigious exhibitions, such as "Permata Youth Photostory" organized by Permata Photojournalist Grant and Pannafoto Institute, Bandung Photography Triennale, Bandung Photography Month, and SEA Reading Photobookdummies in Taiwan. This work is considered a masterpiece by Kurnia Ngayuga Wibowo and serves as a compelling example of experimental photography. The appreciation of such a work is often conducted through art criticism, which plays a crucial role in interpreting and appreciating the underlying content of a photographic work. Understanding and interpreting each photograph can vary significantly, depending on the perspective of the critic or the photographer. The purpose of this research is to explore and analyze the artistic elements and intentions behind the Memory Lane series through the lens of art criticism, specifically using Feldman’s art criticism theory. This qualitative study utilizes Feldman’s four-step approach to art criticism-description, formal analysis, interpretation, and evaluation—to gain a deeper understanding of the photography series. The findings of this research reveal that Memory Lane represents a form of experimental photography, which navigates various challenges inherent to the medium, particularly in terms of storytelling through images. The study demonstrates how art criticism can provide diverse perspectives on a single work of art and how these perspectives can be integrated with other art forms to enrich the overall interpretation. The implications of this research extend to the broader field of art criticism and photography, highlighting the importance of critical analysis in understanding the multifaceted nature of photographic art and its capacity to convey complex narratives.